ChemInform Abstract: Tandem Heck/Decarboxylation/Heck Strategy: Protecting‐Group‐Free Synthesis of Symmetric and Unsymmetric Hydroxylated Stilbenoids. Issue 22 (13th May 2013) - Shard, Amit; Sharma, Naina; Bharti, Richa; Dadhwal, Sumit; Kumar, Rajesh; Sinha, Arun K.
Abstract A sequential Heck reaction of acrylic acid with aromatic halides followed by decarboxylation and a second Heck reaction is developed.